Modified lateral orbital wall decompression in Graves' orbitopathy using computer-assisted planning. Issue 2 (February 2018) - Spalthoff, S.; Jehn, P.; Zimmerer, R.; Rana, M.; Gellrich, N.-C.; Dittmann, J.
Abstract: Graves' orbitopathy, a condition seen in the autoimmune syndrome Graves' disease, affects the fatty tissue and muscles inside the orbit. Graves' orbitopathy is associated with increasing exophthalmos and sometimes leads to compressive dysthyroid optic neuropathy, resulting in progressive vision loss. Dysthyroid compressive optic neuropathy, functional problems, and cosmetic problems are the main indications for surgical decompression of the orbit, especially if conservative treatment has not led to a reduction in symptoms. Many surgical techniques are described in the literature. This article presents a modification of the lateral orbital wall osteotomy, involving the rotation and reduction of the osteotomized bone segment using preoperative planning, intraoperative computed navigation, and piezoelectric surgery. This new method combines the advantages of different techniques and appears to be a valid approach to the treatment of severe cases of Graves' orbitopathy.